Visible Light Photocatalysis: Applications and New Disconnections in the Synthesis of Pharmaceutical Agents - Douglas, James J; Sevrin, Martin J; Stephenson, Corey R. J (Organic process research & development, 2016)
Photoredox catalysis has emerged as a powerful tool for the synthetic chemist to access challenging targets and to generate new structural complexity. This review focuses on the application of this mode of catalysis to arrive at known pharmaceutically active compounds. Within this setting, the growing synergy with other modes of catalysis, such as nickel/photoredox dual catalysis, as well as pioneering examples utilizing continuous flow to transition photoredox catalysis to preparative scale will be highlighted.